1993
DOI: 10.1021/bi00092a001
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced dissociation of fluorescein from the anti-fluorescein single-chain antibody 4-4-20

Abstract: Hydrostatic pressure was used to dissociate fluorescein (Fl) from the high-affinity anti-Fl single-chain antibody 4-4-20 (SCA 4-4-20). Fl dissociation was monitored by measuring (1) the shift in the Fl absorption peak, (2) the recovery in Fl fluorescence intensity, which is quenched upon SCA binding, or (3) the decrease in Fl fluorescence polarization. Pressure effects were studied at two different Fl:SCA 4-4-20 molar ratios: 1:1, at which Fl fluorescence quenching was ca. 35% at atmospheric pressure, and 1:5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…The quenching decreased with pressure as seen in the figure. In the previous paper [24], we have calculated the standard volume change associated with the dissociation of FL and IgG-49 from the FL-IgG-49 complex and obtained the value of −5.2 cm 3 mol −1 , that is, the complex expands slightly by binding of them. Similar dissociation behavior of anti-fluorescyl [25][26][27] and anti-BSA [28] monoclonal antibodies by pressure has been observed, and our value is close to the value reported for the anti-fluorescyl monoclonal antibody with a strong affinity to FL by Herron et al [15]. The value decreased with increasing temperature.…”
Section: Pressure Effect On the Interaction Of Igg-49 With Inhibitorssupporting
confidence: 91%
“…The quenching decreased with pressure as seen in the figure. In the previous paper [24], we have calculated the standard volume change associated with the dissociation of FL and IgG-49 from the FL-IgG-49 complex and obtained the value of −5.2 cm 3 mol −1 , that is, the complex expands slightly by binding of them. Similar dissociation behavior of anti-fluorescyl [25][26][27] and anti-BSA [28] monoclonal antibodies by pressure has been observed, and our value is close to the value reported for the anti-fluorescyl monoclonal antibody with a strong affinity to FL by Herron et al [15]. The value decreased with increasing temperature.…”
Section: Pressure Effect On the Interaction Of Igg-49 With Inhibitorssupporting
confidence: 91%
“…This indicated that Fv 4-4-20 displayed the same standard volume change (⌬ diss : Ϫ50 ml/mol) upon fluorescein dissociation as SCA (38). Seeing that their structures were apparently identical, this suggested that the Fv 4-4-20 must have increased conformational dynamics relative to the IgG molecule (⌬ diss : Ϫ5 ml/mol) as originally postulated for SCA (15,38,41). This indicated that increased dynamics were responsible for the decreased affinity for antigen displayed by Fv and SCA.…”
Section: Comparative Analysis Of Sca and Fv 4-4-20mentioning
confidence: 82%
“…As previously stated, hydrostatic pressure does not promote changes on the tertiary structure of proteins, but alters regions of secondary structure responsible for global protein conformation (38,66). A comparison of the pressure induced dissociation of fluorescein profiles for Fv and SCA would be a definitive evaluation of their dynamic similarity.…”
Section: Comparative Analysis Of Sca and Fv 4-4-20mentioning
confidence: 93%
See 1 more Smart Citation
“…Molecular interactions destabilized by cold are those driven by the entropic component of the free energy of association, [22,23] whereas, this entropic component is usually derived from the favorable contribution of the hydrophobic effect. [24] Laminin self-polymerization in neutral pH is an entropically driven process.…”
Section: Effect Of Temperature and Time On Polylm Stabilitymentioning
confidence: 99%